2018
DOI: 10.3390/ijms19103247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of OsCDPK1 on the Structure and Physicochemical Properties of Starch in Developing Rice Seeds

Abstract: Overexpression of a constitutively active truncated form of OsCDPK1 (OEtr) in rice produced smaller seeds, but a double-stranded RNA gene-silenced form of OsCDPK1 (Ri) yielded larger seeds, suggesting that OsCDPK1 plays a functional role in rice seed development. In the study presented here, we propose a model in which OsCDPK1 plays key roles in negatively controlling the grain size, amylose content, and endosperm appearance, and also affects the physicochemical properties of the starch. The dehulled transgeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In leaves, AGPases are known to be plastidial (Pérez et al, 2018). Furthermore, it has been shown that the grain size is altered when the starch structure changes (Matsushima et al, 2016; Wang, Zhang et al, 2018; Jiang et al, 2018). Hence, the expression of genes known to regulate seed size was examined in L_5 and L_6.…”
Section: Resultsmentioning
confidence: 99%
“…In leaves, AGPases are known to be plastidial (Pérez et al, 2018). Furthermore, it has been shown that the grain size is altered when the starch structure changes (Matsushima et al, 2016; Wang, Zhang et al, 2018; Jiang et al, 2018). Hence, the expression of genes known to regulate seed size was examined in L_5 and L_6.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, increasing reports found that ZmCPK32, AtCPK32, and GmCDPK38 as the homologue of TaCDPK23, played important roles in modulating flowering time and pollen tube growth ( Zhou et al., 2014 ; Li et al., 2018 ; Li et al., 2022a ; Li et al., 2022b ), implying that TaCDPK23 probably plays a crucial role in regulating the development of spike/anther at the anthesis stage. OsCDPK1 was proved that it played a functional role in rice seed development ( Jiang et al., 2018 ). As shown in Table S5 , TaCDPK8 and OsCDPK1 are also the homologues with the highest identification 94.2%, which tempt us to speculate that TaCDPK8 perhaps performs the similar functions to OsCDPK1 by regulating the development of ovary/anther at the inforescence stage in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of GmCDPK3 also improved plant tolerance to drought as well as salt stresses ( Wang et al., 2019b ). Besides these, OsCDPK1 also conferred drought tolerance in rice seedlings besides of its functions in seed development ( Ho et al., 2013 ; Jiang et al., 2018 ). Based on the inducible expression profile of TaCDPK2 , the high identification between TaCDPK2 and OsCDPK13 with 95.9%, we speculate that TaCDPK2 perhaps play the potential role in plant response to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of chalkiness is a complex process, and the formation of chalkiness may involve the relationship between "source", "sink" and "flow" in rice plants. Any change in any one of the three or the disharmony of their relationship may lead to or increase the formation of Chalkiness in rice endosperm (Jiang et al, 2018;Nevame et al, 2018;Huang et al, 2020).…”
Section: Identifmentioning
confidence: 99%